Extraction and quantification of eugenol from clove buds using HPLC - Shafira, Khadiza Fitri; Azad, Abul Kalam; Labu, Zubair Khalid; Helal Uddin, A.B.M. (Bentham Science, 2020)
Background: Eugenol is the main constituent of clove essential oil. Past studies have found that clove oil has diverse uses in the pharmaceutical field due to its antioxidant, antibacterial and anesthetic properties. Objective: This work compares the performance of different extraction methods and factors and identifies the effect of the treatments on oil yields and eugenol content. Materials and Methods: Maceration, Hydro distillation, microwave-assisted extraction (MAE),and Soxhlet were performed. The best technique was identified according to yield and content. Further studies were conducted to examine the effects of different factors, such as solvent types (ethanol and methanol) and sample-to-solvent ratio (1:10 and 1:15). HPLC UV-Vis was utilized in the analysis of eugenol concentration. Results and Discussion: Soxhlet extraction provided the highest yield (39.98%) and eugenol con- tent (15.83%), compared to other methods. The results observed from several Soxhlet extraction factors showed that there is no significant difference between the different factors. In the mean- time, methanol 1:15 provided the greatest amount of yields (57.83%) and eugenol content (22.21%). In this regard, the higher ratio resulted in higher eugenol content. Conclusion: The results obtained are less comparable because the processing time, the working sol- vent, and the separation technique were carried out differently for each method. In the meantime, as there is no past study that compared the selected methods and factors, this study’s findings will contribute substantially to fill the gap in this field.